The role of local participation in the governance of natural resource extraction - Kurniawan, Nanang Indra; Lujala, Päivi; Rye, Ståle Angen; Vela-Almeida, Diana (Elsevier Ltd, 2022)
This article introduces the special section on "The role of local participation in the governance of natural resource extraction". It highlights the inherent conflicts between official techno-regulatory and corporate schemes for citizen engagement and bottom-up, community-led participatory mechanisms for decision-making in extractive governance. This special section offers empirically and theoretically innovative analyses of participatory processes in extractive sectors in the Americas. This brief introduction highlights the need to study how 'local demands' are conceptualized within participatory frameworks and examine what role affected populations play in resisting and shaping transnational extractive policies and practices. © 2021 The Authors